Risk of Teenagers’ Pre-Marital Sexual Behavior in Boarding Houses - Sinthia Rosanti Maelissa (Global Health Science Group, 2020)
The social environment nowadays offers many options for young people. Dating styles that present opportunities for premarital sexual behavior among adolescents become an attractive offer, especially for teens who live in boarding houses. Residing in a boarding house without direct supervision from parents and landowners causes teens to liberally engage in a premarital sexual behavior with their partners, thus making boarding houses an unsafe environment for them. This study used Descriptive Phenomenology Design which aimed to comprehensively investigate the risks of premarital sexual behavior among adolescents living in boarding houses. The number of participants in this study was 6 people until data saturation was reached. The analysis in this study used selective techniques and focusing analysis resulted in 3 themes, i.e.: 1) the desire to experiment, 2) social demands and 3) places to live with potential risk. The drives from within, social demands from friends, and places with high possible risk become the causes of premarital sexual behavior in boarding houses. The results of the study encourage community nurses to improve adolescents’ screening through health programs in schools and PKPR for teenagers who live in the boarding houses.